2017
DOI: 10.1590/2177-6709.22.5.039-046.oar
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hard tissue surgical changes on soft tissue displacement: a pilot CBCT study

Abstract: Introduction: This pilot study had as main objective to test the reliability of a new method to evaluate orthognathic surgery outcomes and also, to understand the effect of hard tissue changes on soft tissue displacement. Methods: The sample consisted of eight patients that underwent bimaxillary advancement and had CBCT at two time points (before surgery and 6-8 months follow-up). Voxel-based cranial base superimposition was used to register the scans. A different technique of iterative closest point (ICP) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…A previous study indicated that CBCT overcomes the limitations of 2D radiographs without exposing the patient to high levels of radiation, and allows the simultaneous evaluation of hard and soft tissues [28]. In recent years, the evaluation of soft tissue displacement using CBCT has become more common [17,18,[29][30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study indicated that CBCT overcomes the limitations of 2D radiographs without exposing the patient to high levels of radiation, and allows the simultaneous evaluation of hard and soft tissues [28]. In recent years, the evaluation of soft tissue displacement using CBCT has become more common [17,18,[29][30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…We found facial soft tissue changes in both the upper face and lower face regions with a mean of 0.77 ± 0.51 and 0.67 ± 0.38 mm respectively, while the mean deviation at the nasal region was 1.03 ± 0.14 mm. Previous studies of maxillary advancement and mandibular setback reported more soft-tissue movement in the central parts than in the lateral parts [25]. While Gjorup et al found that no changes occurred in the cheeks, they took into consideration that the influence of the muscles and soft tissue tension decreased as the distance from the area where the hard tissue changes increased [20].…”
Section: Soft Tissue Changesmentioning
confidence: 98%
“…The sample size was determined based on the findings of a previous study by Koerich and colleagues (109). The extent of skeletal movement achieved using the treatment plan was (3.87±1.6mm) for the maxillary advancement, and (3.46±1.34mm) for the mandibular setback.…”
Section: Subjectsmentioning
confidence: 99%